If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 2B + g Solving 24 = 2B + g Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-2B' to each side of the equation. 24 + -2B = 2B + -2B + g Combine like terms: 2B + -2B = 0 24 + -2B = 0 + g 24 + -2B = g Add '-24' to each side of the equation. 24 + -24 + -2B = -24 + g Combine like terms: 24 + -24 = 0 0 + -2B = -24 + g -2B = -24 + g Divide each side by '-2'. B = 12 + -0.5g Simplifying B = 12 + -0.5g
| (0,3/0,01)*2*((0,2*1,9*10^3)/(N*0,3*0,9))^(1/3)*(12/6)^(0,14) | | 4a^2-20a-24=0 | | 3x+5y+2z=2 | | -p^2+p+20=0 | | 4e=24 | | -3p-(-3)/-6=-12 | | 36=9m | | 7x-11/5x-2=2x-9/5x-2 | | 2x=9-5x+32 | | t+8=4t+5 | | 8z-6=7z | | ((x^2-ax-8)/(x-a))=0 | | 8(x-8)=4(x+4) | | (3x-4)(2x+5)=20 | | N^(2/3)=12,5 | | 2x+46=320 | | 5x+6+4x=-3(x-8)+7x | | (3.0075-6.0215)+t=2.105 | | x^3-x^2+2x-1=0 | | -5x+3=-6-2x | | 11(v+1)-3v=4(2v+4)-25 | | 3x-7x=-8 | | 2.7(x-8)=-2.7(x+15) | | 28y^2+40y-80=-32y-64 | | 7y^2+10y-20=0 | | -(-9x^2-8x+8)= | | 28y^2+40y-80=0 | | (-9x^2-8x+8)= | | f(x)=9p^2-24pk+16k^2 | | 8x+3-11x=(-9) | | 39=3y-4 | | -12r+3+r=-19 |